GE_GERICHTE C/868/2013 vom 6. März 2015 - GE Cour de justice (2015)
OBLIGATION D'ENTRETIEN; ENFANT; OBLIGATION D'ENTRETIEN; CONJOINT; RENTE D'INVALIDITÉ; AVANCE DE FRAIS; CONJOINT | CC.125.1; CC.285.1; CPC.317.1